-4(v+2)+2v+7=7v+12

Simple and best practice solution for -4(v+2)+2v+7=7v+12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4(v+2)+2v+7=7v+12 equation:


Simplifying
-4(v + 2) + 2v + 7 = 7v + 12

Reorder the terms:
-4(2 + v) + 2v + 7 = 7v + 12
(2 * -4 + v * -4) + 2v + 7 = 7v + 12
(-8 + -4v) + 2v + 7 = 7v + 12

Reorder the terms:
-8 + 7 + -4v + 2v = 7v + 12

Combine like terms: -8 + 7 = -1
-1 + -4v + 2v = 7v + 12

Combine like terms: -4v + 2v = -2v
-1 + -2v = 7v + 12

Reorder the terms:
-1 + -2v = 12 + 7v

Solving
-1 + -2v = 12 + 7v

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '-7v' to each side of the equation.
-1 + -2v + -7v = 12 + 7v + -7v

Combine like terms: -2v + -7v = -9v
-1 + -9v = 12 + 7v + -7v

Combine like terms: 7v + -7v = 0
-1 + -9v = 12 + 0
-1 + -9v = 12

Add '1' to each side of the equation.
-1 + 1 + -9v = 12 + 1

Combine like terms: -1 + 1 = 0
0 + -9v = 12 + 1
-9v = 12 + 1

Combine like terms: 12 + 1 = 13
-9v = 13

Divide each side by '-9'.
v = -1.444444444

Simplifying
v = -1.444444444

See similar equations:

| f(x)=-x^2-48 | | -(-x+18)= | | 8x+7=-3(5x-4) | | y*2+9y*2= | | m-15=3(m-4)-2m | | 617=25k-8 | | 9(p-8)=18 | | 3m+2m=8 | | x-1+15=x-1+9 | | -x+8y=-32 | | 5(x-3)+8=7x-10 | | 4-4x=-3x | | 18(k+12)=936 | | 2x+3x+3x+32=360 | | 14(x+30)=-196 | | v/9-5=(-6) | | z2=9/16 | | 19=-9(8c-3) | | 7v+1+6v= | | 2g+2g-4=43 | | 3-3(x-4)=-3-2 | | b/9=3 | | -3(x+7)=6x-39 | | -10+9k=62 | | 5x^2-14x-76=0 | | x-.10x=150 | | 7(8x+8)=56x-1 | | 13-50=20(5x-9x)+6x | | -1-(-12)= | | 8t/6 | | 2*15/7 | | cbrt(2x-3)=3 |

Equations solver categories